EEG in Rett's Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1987)
The electroencephalographic (EEG) characteristics of Rett's syndrome were studied in 17 girls between the ages of 1 and 16 yrs at the Sections of Neurophysiology and Pediatric Neurology, Baylor College of Medicine and The Methodist Hospital, Houston, TX.